2007
DOI: 10.1176/appi.ajp.164.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Clinical Predictors of Suicidal Acts After Major Depression: A Prospective Study

Abstract: Objective-Whether sex differences exist in clinical risk factors associated with suicidal behavior is unknown. The authors postulated that among men with a major depressive episode, aggression, hostility, and history of substance misuse increase risk for future suicidal behavior, while depressive symptoms, childhood history of abuse, fewer reasons for living, and borderline personality disorder do so in depressed women.Method-Patients with DSM-III-R major depression or bipolar disorder seeking treatment for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(44 citation statements)
references
References 48 publications
4
40
0
Order By: Relevance
“…Statistically significant associations similar to those between smoking and suicide deaths have been documented between smoking and SROs in cross-sectional810 and prospective9, 11 studies in both general population samples810, 12 and clinical samples 13, 14. These associations have held up after controlling for socio-demographics and limited measures of psychological functioning (including measures of depression and drug use disorders).…”
mentioning
confidence: 67%
“…Statistically significant associations similar to those between smoking and suicide deaths have been documented between smoking and SROs in cross-sectional810 and prospective9, 11 studies in both general population samples810, 12 and clinical samples 13, 14. These associations have held up after controlling for socio-demographics and limited measures of psychological functioning (including measures of depression and drug use disorders).…”
mentioning
confidence: 67%
“…Several studies have assessed suicide risk factors in unipolar and bipolar disorders (Fawcett et al , 1990; Krupinski et al , 1998; Schneider et al , 2001; Angst et al , 2002; Oquendo et al , 2007; Tondo et al , 2007), and some have conducted separate analyses by polarity (Black et al , 1988; Kallner et al , 2000; Angst et al , 2005a). An assumption of the former studies is that risk factors do not vary by diagnosis and the latter studies do little to validate this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…Depression severity (Roy, 1993), comorbid personality (Corbitt et al, 1996; Soloff et al, 2000), anxiety (Bolton et al, 2008; Stein et al, 2001), and alcohol use disorders (Bulik et al, 1990; Claassen et al, 2007) have all been associated with an elevated risk of suicide attempt. Longitudinal studies have consistently demonstrated the importance of past suicide attempts (Oquendo et al, 2005; Oquendo et al, 2007; Sokero et al, 2005), cigarette smoking (Oquendo et al, 2005; Oquendo et al, 2007), alcohol use disorders (Maser et al, 2002), and comorbid personality disorder (Hansen et al, 2003; Oquendo et al, 2007) as predictors of future suicide attempts in depressed populations.…”
Section: Introductionmentioning
confidence: 99%